Significant association between Let-7-KRAS rs712 G > T polymorphism and cancer risk in the Chinese population: a meta-analysis - Du, Xin-Ya (Oncotarget, 2017)
Association between let-7-KRAS rs712 polymorphism and cancer risk was inconsistent. We therefore conducted this meta-analysis to clarify the association between let-7-KRAS rs712 polymorphism and cancer risk with STATA 14.0 software. A systemic literature search in online databases (PubMed, Embase, CNKI and Wanfang database) was preformed to obtain relevant articles. A total of 13 case-control studies involving 3,453 patients and 4,470 controls were identified up to May 16, 2015. The pooled results indicated that significantly increased risk were observed in Chinese population in T vs. G (OR = 1.21, 95% CI = 1.03–1.42) and TT vs. GG + GT genetic models (OR = 1.69, 95% CI = 1.17–2.42). Sensitivity analysis was conducted and the result without heterogeneity showed significant associations in all five genetic models. Subgroup analyses of cancer type indicated a similar result in digestive cancer (for T vs. G: OR = 1.41, 95% CI = 1.26–1.57; GT vs. GG: OR = 1.24, 95% CI = 1.07–1.43; TT vs. GG: OR = 2.53, 95% CI = 1.86–3.44; GT + TT vs. GG: OR = 1.36, 95% CI = 1.19–1.56; TT vs. GG + GT: OR = 2.35, 95% CI = 1.73–3.19). In summary, these evidences demonstrate that let-7-KRAS rs712 G > T polymorphism might be associated with digestive system cancer risk in the Chinese population.